2012
DOI: 10.1143/jpsjs.81sa.sa020
|View full text |Cite
|
Sign up to set email alerts
|

Application of Phase Transition Theory to a Glass-Forming System

Abstract: We have investigated the crystallization of a monatomic simple liquid in equilibrium, where the constituents interact through the Lennard-Jones-Gauss (LJG) potential. By incorporating a perturbation expansion into a density functional approach, we obtain a phase diagram covering a wide range of the parameter space. The phase diagram agrees qualitatively with that obtained by molecular dynamics (MD) simulations. The MD simulations show that the system cannot be crystallized, even if the temperature is sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The size ratios of q = 1/10 and 1/6 were examined to study the effects of the second minimum on the IE potential because the coexistence densities are affected by the location of the second minimum (see fig. 1) in the previous results for the Lennard-Jones-Gauss systems [37][38][39]. Here, the second minimum for q = 1/6 was located at the peak of g HS LL (r) of the bcc crystal.…”
supporting
confidence: 55%
See 4 more Smart Citations
“…The size ratios of q = 1/10 and 1/6 were examined to study the effects of the second minimum on the IE potential because the coexistence densities are affected by the location of the second minimum (see fig. 1) in the previous results for the Lennard-Jones-Gauss systems [37][38][39]. Here, the second minimum for q = 1/6 was located at the peak of g HS LL (r) of the bcc crystal.…”
supporting
confidence: 55%
“…It seems that the contribution of the second minimum in the potential φ ef f (r) is not always small. It has been shown that the second minimum affects the coexistence density and pressure in the Lennard-Jones-Gauss system [37][38][39]. The second peak of g HS LL (r) around r = 1.17σ l is large for a bcc crystal (fig.…”
mentioning
confidence: 98%
See 3 more Smart Citations